Meningkatkan Hasil Belajar Siswa Pada Notasi Sigma, Barisan Dan Deret Melalui Model Pembelajaran Kooperatif Tipe Jigsaw Di Kelas XII IPA I S ekolah M enengah A tas Negeri I Muaro Jambi - ANCE ERIPIANA TAMBUNAN (STIT Muhammadiyah Paciran Lamongan, 2019)
Abstract : The math learning process in XII IPA SMAN 1 Muaro Jambi had been run ineffectively that had affected on unsatitissfied learning’s result. Besides, the laxk of students’ willing on learning were identifying through the learning motivation, learning process interaction dan students’ learning readiness and the results of learning. This action reaseach purposes to explore the Jigsaw model for cooperative learning is able to to improve student’s learning result pn sigma notation concepts, sequences, and series. This study conducted in XII 1PA 1 SMAN 1 Muaro Jambi in 3 phases. The result of study shows that the Jigsaw model can improve learning process whereas the first phase 20 students passed in learning, the second phase 25 students achieved the learning score, and the last past 34 students rose the learning score